2018
DOI: 10.3389/fphar.2018.00443
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Akt/mTOR/p70S6K Signaling Activity With Huangkui Capsule Alleviates the Early Glomerular Pathological Changes in Diabetic Nephropathy

Abstract: Huangkui capsule (HKC), a Chinese modern patent medicine extracted from Abelmoschus manihot (L.) medic, has been widely applied to clinical therapy in the early diabetic nephropathy (DN) patients. However, it remains elusive whether HKC can ameliorate the inchoate glomerular injuries in hyperglycemia. Recently the activation of phosphatidylinositol-3-kinase (PI3K)/serine-threonine kinase (Akt)/mammalian target of rapamycin (mTOR) signaling and its downstream regulator, 70-kDa ribosomal protein S6 kinase (p70S6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 43 publications
1
39
0
Order By: Relevance
“…One capsule of HKC contains 0.5 g of AM and 34 mg of TFA. Our previous animal experiment revealed that a 2 g/kg/day dose of HKC, which contains a 136 mg/kg/day dose of TFA, can significantly attenuate renal fibrosis (Wu et al, 2018). Thus, the rats in the TFA group received a TFA suspension at a dosage of 136 mg/kg/day.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…One capsule of HKC contains 0.5 g of AM and 34 mg of TFA. Our previous animal experiment revealed that a 2 g/kg/day dose of HKC, which contains a 136 mg/kg/day dose of TFA, can significantly attenuate renal fibrosis (Wu et al, 2018). Thus, the rats in the TFA group received a TFA suspension at a dosage of 136 mg/kg/day.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…The incidence of DM has been increasing worldwide and as a secondary complication, DN is one of the most significant causes of end-stage renal disease (29,30). In China (31) and the United States (32), ~16 and 26% of patients with DN develop end-stage renal disease, respectively; thus, effective and safe treatment strategies to delay the progression of DN are urgently required in the clinic (21). However, little progress has been made in the treatment of patients with DN (33).…”
Section: Discussionmentioning
confidence: 99%
“…However, only mTORC1 is sensitive to rapamycin inhibition, and controls cell proliferation and growth via the phosphorylation of certain downstream targets, such as ribosomal protein S6 kinase β-1 (p70S6K) (20). Aberrant activation of the mTORC1/p70S6K pathway has been reported to be involved in the pathogenesis of DN (21). Furthermore, mTORC1/p70S6K signaling may mediate renal tubular EMT during DN (19).…”
Section: Introductionmentioning
confidence: 99%
“…for 28 days) dramatically reduced urinary microalbumin levels, increased body weight and serum albumin levels, improved renal morphology and kidney weight, reduced the kidney hypertrophy index, alleviated glomerular hypertrophy, decreased the expression of α-smooth muscle actin and proliferating nuclear cell antigen, and decreased thickening of the glomerular basement membrane. The mechanism explored demonstrated that HKC downregulated the protein expression of p-p70S6K, p-mammalian target of rapamycin (mTOR), TGF-β1, and p-Akt by repressing the phosphoinositide-3-kinase (PI3K)/Akt/mTOR/p70S6K signaling pathway in the kidneys of rats in a model of early DN ( Wu et al., 2018 ). In agreement with the results of the in vivo study, hyperoside, which is a bioactive component of HKC, at concentrations of 5 and 15 µg/mL significantly downregulated the protein expression of p-Akt, p-mTOR, p-PI3K, and p-p70S6K in murine mesangial cells induced by high glucose levels in vitro ( Wu et al., 2018 ), which suggested that HKC safely and efficiently alleviates early pathological changes in the glomeruli in DN by inhibiting the PI3K/Akt/mTOR/p70S6K signaling pathway in vivo and in vitro and provides reliable evidence of the prevention of early DN.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%